(untitled) (Journal of Science and Technology, 2016)
Digestion conditions of the bauxite were studied using four different samples from the Kibi deposit. The samples were digested at 140°C and 240°C employing. liquor concentrations between 140 and 200 kg.m4 as sodium oxide. Results indicated the the digestion efficiency was low (61-77%) for digestion at 140°C. This was probably due to the insolubility of substantial amounts of boehmite present in some of the bauxite samples and, to some ’degree, to the gibbsite-boehmite transformations under these conditions. Digestion efficiency at 240°C was high (above 80%), especially for liquor concentrations of 160kg.m4 and above, because of the dissolution of boehmite. Energy analysis of the various digestion conditions showed that percentage primary heating energy for the high temperature digestion was low, but in absolute terms higher than for low temperature digestion. Settling tests indicated that because the rather coarse dispersions of the boehmite and geothite phases remained unchanged at 140°C, settling properties of the bauxite residue were better than for digestion at 240°C.